Practitioners’ perception of value in construction - Wandahl, Søren (Journal of Civil Engineering and Management, 2015)
Value delivery is basically the main purpose of construction, and in fact it is not the physical construction in itself that a client buys but the attributes or value the building provides. This value delivery is undertaken in a complex endeavour of collaboration. Throughout a building project value is in focus both implicit and explicit. Often challenges or direct problems arise during the process, which may be due to an incongruent perception of value. A survey was conducted among practitioners of the Danish building industry, aiming at investigating whether or not practitioners perceive value differently. The survey revealed that the practitioners had a diverse understanding of how to perceive value in a building project. This is problematic for the efficiency and effectiveness of building projects. Value is the underlying concept of emerging methods and concepts such as Lean Construction, Value Management and Partnering. When a homogeneous understanding of value does not exist, the full potential of applying value based concepts will not occur.